The Influence Of Social Media On Waqf Funding In BPW Ar Risalah - Wahyuni, Hilmi; Yani Rilianti, Fitri; Afiatika, Afina; Isyrahlia, Isyrahlia; Achta Pratama, Fahmi; Wahyudi, M. (Risalah Iqtisadiyah: Journal of Sharia Economics, Sharia Economics Study Program, STEI Ar Risalah Sumatera Barat, 2024)
Waqf is a philanthropic instrument in Islam which plays an important role in improving community welfare. With the development of digital technology, the concept of digital-based cash waqf has become a new trend in collecting waqf funds through platforms such as websites, applications and social media. This research aims to analyze the influence of social media on waqf funding at the Ar Risalah Waqf Management Agency (BPW). This research is a quantitative research using observation methods to collect data on the number of social media posts (variable and simple linear regression analysis. The results of the research show that social media does not have a significant influence on the number of wakifs with a significance value of 0.078 > 0.05, even though the correlation coefficient value is in the low category (R = 0.359), social media has a coefficient of determination (R Square) value of 12.9 % means that social media contributed 12.9% to 12.9% of the total number of wakifs. These findings contribute to the understanding of the role of social media as a means of promoting and collecting waqf funds and provide insight for waqf management institutions to formulate more effective strategies in utilizing digital technology. This research also opens up opportunities for further exploration of other factors that can encourage the success of collecting waqf funds through digital platforms.